Silver nanoparticles: Green Synthesis and Their Antibacterial efficiency - Dung, Ngo Thanh; Tam, Le Thi Thanh; Nguyet, Ha Minh; Lu, Le Trong (Vietnam Journal of Science and Technology, 2021)
In this study, silver nanoparticles were synthesized from aqueous silver nitrate through a simple and eco-friendly route using a combination of two reducing agents: sodium citrate and tannic acid. By this method, the obtained Ag nanoparticles (NPs) were stable within the studied period of six months. Besides, both TEM images and UV-Vis results showed that the size of silver NPs could be controlled by changing the concentration of tannic acid. The antibacterial ability of Ag NPs with different sizes were also examined. In detail, the smaller the Ag NPs were, the more efficient their antibacterial activity was.